The Effect of Trade Openness on Income Inequality with the Role of Institutional Quality - Lim Thye Goh; Siong Hook Law (Indonesian Journal of Economics, Social, and Humanities, 2019)
This study investigates the effect of trade openness on income inequality using the panel system generalised method of moments (GMM). The sample countries consist of 65 developed and developing countries and the time period covers from 1984 to 2012. This study also provides new evidence that sheds light on the role of institutional quality in influencing the effectof trade openness on income inequality. The empirical results reveal that trade openness tends to increase income inequality. In addition, the marginal effect also revealed that institutional quality has a corrective effect on the trade openness – income inequality nexus.